Laparotomy enables retrograde dilatation and stent placement for malignant esophago-respiratory fistula - Iskender Özcan (World Journal of Surgical Oncology, 2008)
Abstract Background Malignant esophageal stenosis with complete obstruction and esophagorespiratory fistula (ERF) is difficult to treat with standard endoscopic techniques. Case presentation We report a patient in whom with local recurrence of esophageal carcinoma an esophagotracheal fistula occurred. Initially the patient had undergone esophageal resection with interposition of a gastric tube. Due to complete obstruction of the lumen by recurrent tumor conventional transoral stent placement failed. For retrograde dilatation a laparotomy was performed. Via a duodenal incision endoscopic access to the gastric tube was achieved. Using a guidewire the esophageal obstruction was traversed and dilated. Then it was possible to place an esophageal stent via an antegrade approach. Conclusion Open surgery enables a safe access for retrograde endoscopic therapy in patients who had undergone esophageal resection with gastric interposition.